Perhatian Orangtua dan Motivasi Belajar Siswa Sekolah Dasar - Deisye Supit (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This research is aquantitative research that is descriptive and correlational. Parental attention is a form of support given by parents to increase student motivation in learning. This research is to find out the relationship between parental attention and students' learning motivation. Data collection using random sampling method. This research was conducted at SMP N 9 Dumoga with 75 respondents in class VII and VII SMP students who were active in the 2020/2021 academic year. To determine the level of people's attention and students' motivation to learn, the mean score was used. To find out whether there is a significant relationship between parental attention and student motivation, Pearson correlation is used. From the results of research conducted at SMP 9 N Dumoga that parental attention is high with a mean = 3.04, and has student motivation in learning science, where the average value = 4.50. The results conducted at SMP N 9 Dumoga showed that there was a significant relationship between parental attention and student motivation. Because the results of this study indicate that p value = 0.034 > = 05. The correlation value = 0.254 means that there is a significant relationship between parental attention and student motivation.